A Comparative Analysis Between the Juvenile Justice Process of Bangladesh and China - Khan, Md. Bashir Uddin (2018)
Juvenile delinquency is an issue of concern all over the world. It has long been an issue of discussion throughout the world among the legal scholars, psychologists, and world leaders. Many international conventions and treaties, therefore, are still in action to deal with the problem. These legal guidelines are set as the standard of the rights for the juveniles or children who come in contact or conflict with the law. The pattern of the delinquency, the definition of activities as delinquency and crimes and other associated issues are not equal in all the countries of the world. Western countries are clearly ahead in establishing a more liberal justice system for the juveniles than other countries. Some Asian countries are also concerned with the issue and continuously striving to change their system as per the guidelines of the international legal instruments. China has also undergone a considerable headway in the present years in reducing the delinquency adopting new measures in this regard. Bangladesh, on the other hand, enacted a new legal framework replacing the old one to create a more congenial environment for the juveniles. As a result, the juvenile justice system in both of these countries is achieving new dimensions. A comparative study between these two countries reveals that there are some differences in the ways of dealing with the juveniles who come in the contact or conflict with the law. China’s juvenile justice system is mostly criminal in nature where argumentative ways of prosecution are prevalent. On the other hand, seemingly the process of Bangladesh is more favourable for the juveniles. Both of these countries emphasise on the rehabilitation process while China has formally established that their means of handling juveniles will primarily be through the education followed by the punishment. Both of these countries need to establish many specialized treatment centres so that the juveniles can be rehabilitated properly under necessary supervision. Chinese Procuratorate system is also a good one that works like a circuit breaker in stopping mass and whimsical arrest of juveniles by police officers. This study, however, is based on content analysis and was conducted between January 2018 to March 2018.Keywords: Criminal justice system, international legal instruments, Beijing rules, comparison, dissimilaritie